2022
DOI: 10.1002/alz.12777
|View full text |Cite
|
Sign up to set email alerts
|

Anosmia, mild cognitive impairment, and biomarkers of brain aging in older adults

Abstract: Olfactory impairment is a potential marker for prodromal dementia, but the underlying mechanisms are poorly understood. This population-based study included 4214 dementia-free participants (age ≥65 years). Olfaction was assessed using the 16-item Sniffin' Sticks identification test. In the subsamples, we measured plasma amyloid beta (Aβ)40, Aβ42, total tau, and neurofilament light chain (NfL; n = 1054); and quantified hippocampal, entorhinal cortex, and white matter hyperintensity (WMH) volumes, and Alzheimer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 50 publications
1
34
0
Order By: Relevance
“…Therefore, the main clinical manifestation is non memory dysfunction, such as execution, computation, etc. [28,29] In summary, there are changes in the concentration levels of biochemical metabolites in the hippocampus on both sides of VCIND patients. 1 H-MRS can sensitively detect abnormal metabolic changes in the brain of VCIND patients, which is helpful for early diagnosis and disease monitoring.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, the main clinical manifestation is non memory dysfunction, such as execution, computation, etc. [28,29] In summary, there are changes in the concentration levels of biochemical metabolites in the hippocampus on both sides of VCIND patients. 1 H-MRS can sensitively detect abnormal metabolic changes in the brain of VCIND patients, which is helpful for early diagnosis and disease monitoring.…”
Section: Discussionmentioning
confidence: 96%
“…A previous cross-sectional study examined the associations of OD with plasma Aβ42, Aβ40, the Aβ42/Aβ40 ratio, ttau, and NfL, and found significant results with only t-tau and NfL. 18 Whether AD pathology plays a role in the relationship of OD and cognitive deterioration deserves further investigation. Fifth, we did not take Parkinson's disease (PD) or α-synuclein pathology into consideration when analyzing the relationship of OD, NfL, and cognitive decline.…”
Section: Discussionmentioning
confidence: 96%
“…Faster olfactory decline could predict smaller olfaction‐ and AD‐associated brain regions 9 . Of note, one cross‐sectional study measured plasma t‐tau and NfL in 1054 participants and found a linear relationship between olfactory impairment and higher levels of t‐tau and NfL 18 . However, thus far, few studies have tried to disentangle the relationships among olfaction, neurodegeneration, and cognition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations